Hydro-climate research of the late quaternary of the Eastern Mediterranean-Levant region based on speleothems research – A review. (1st October 2019) - Bar-Matthews, M.; Keinan, J.; Ayalon, A.
Abstract: The Eastern Mediterranean (EM) - Levant region is the eastern borderland of the Eastern Mediterranean Sea (EMS). The EMS brings Mediterranean climate zones to the immediate coastal region and hinterland, but away from the influence of the EMS, the region rapidly becomes a desert. Paleoclimate evidence derived from a large number of studies on speleothems from caves located along sharp climatic gradients enables deep insight into the climate in the EM-Levant region. Growth periods and isotopic composition of speleothems from the various climate regimes capture the regional signals of temperature, rainfall amount and vegetation. Speleothems from northern and central Israel grew continuously in areas where present-day annual rainfall is ∼400–500 mm and show that water was always available during glacials and interglacials. These speleothems display a well-defined δ 18 O orbital modulation of glacial and interglacial marine isotope stages (MIS) and show good correlations with the EMS marine records, pointing to strong direct sea-land links. The climatic record indicates relatively drier and cooler glacials but extreme wet peaks during interglacials, mainly MIS 5e between 128–120 ka BP. Pluvial conditions penetrated to the northern, central and southern Negev Desert. The present-day climatic gradient between the different climatic regions existed through interglacials. However, growth periods of speleothems from the northern Negev Desert, from the "rain shadow' desert, and the Dead Sea Basin, suggest that during last glacial the desert boundary moved from its interglacial and present-day position ∼30 km farther south and ∼60 km farther east, due to positive water balance. Highlights: During last glacial the rainfall system from the Eastern Mediterranean Sea penetrated further east by about 60 km, and about 30 km further south. During peak interglacials, mainly MIS 5e, central and northern Israel experienced deluge rainfall conditions. During MIS 5e the Negev Desert experienced clusters of short wet events during otherwise long drought periods. The importance of Monsoon-derived rainfall in the Southern Levant is still not resolved. The overall present-day climate zones of the EM - Levant region were established during mid-late Holocene.